The Teacher's role in Inclusive Education of Deaf Students in High School (Research, Society and Development, 2020)
The inclusion of people with disabilities in the school environment has become a major challenge for teachers, as this process of inclusion of students requires the construction of new teaching proposals, and the performance of teachers with a different look in the classroom. being the facilitating agent of the teaching-learning process. In view of this factual framework, the present work aims to evaluate the level of preparation and knowledge of the teacher in the process of inclusion of deaf students in the classroom. Thus, we established the Edson High School Technical and Integral School as a research field. Luiz Cavalcante de Gouvêa located in the municipality of Iguatu Ceará, is considered a “B” type school with 396 students enrolled in the 1st to 3rd grades of high school, with 10 classes working full time. We opted for this school, because it counts on its clientele, deaf students included, being this the main reason of the research. It is noted that the teachers' knowledge of the Brazilian Sign Language (LIBRAS) is 67% satisfactory to do a good job with the deaf students enrolled. Given these results, for these students to be included, it is necessary to use pedagogical strategies for satisfactory learning to occur.